Village Head Leadership Function in Teratrai Village Marisa District Pohuwato - Umar Sune; Rusni Djafar; Rival Ismail (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
The purpose of this study is to find out the Leadership Function of the Village Head in Teratrai Village of Marisa District of Pohuwato District This research was carried out for approximately 2 months. This type of research author chooses a type of descriptive research with a qualitative approach, which is research that aims to provide an overview of the application of the principle of good governance in The Lotus Village of Marisa District of Pohuwato Regency. Informants as many as 13 informants consisting of the village head and the device 11 people and the community 2 people. Research Results: 1) Instructive Function, Lotus Village Head has been shown through communication that has been built with the apparatus intensely so that this function takes place well, where the Village Head as the person in charge of the implementation of government in charge of the implementation of government communicates intensely with all the apparatus in the Village, through the implementation of the duties and functions of each apparatus. 2). Consultative Function, Implementation of the consultative function of the Lotus Village Head has been carried out well by the Village Head with all elements and apparatus as implementers of government administration in Lotus village. 3) Participation Function, Leadership of Lotus Village Head can be described through the partition function that in leading and carrying out the election in Lotus Village trying to involve people actively in the administration of government. The people in question are village officials who become co-workers in the Lotus village government organization. The apparatus is involved in every policy taken through the contribution of thoughts, ideas and direct involvement in the implementation of village government. Exchanging information in each policy carried out jointly.4) Delegation Function, the Village Head performs this function in accordance with the expectations of all elements in the village. 5). Lotus Village Head Control Function carries it out through the provision of work responsibilities to the village apparatus accompanied by supervision in carrying out the duties and authorities carried out by the Village apparatus.